Assessment of the sanitary quality of fresh miki from selected processor and retailers in Iloilo wet markets - Fabela, Francis Ben F. (Iloilo SOTECH, University of the Philippines in the Visayas, 1992)
A fresh miki processor from Pavia and its 4 highest retailers from 4 different wet markets in Iloilo were selected as respondents and source of the fresh miki samples for sanitary quality evaluation.
Sotech thesis.
Keywords: Miki; Fresh miki